Penggunaan Multimedia Untuk Peningkatan Hasil Belajar Peserta Didik Pada Mata Pelajaran IPAS Di Kelas V SDN Pelandakan 2 - Akdila Praka Utami; Nugraha Permana Putra; Nila Novi Marliana (CV.ITTC INDONESIA, 2024)
The rapid development of the time and technology requires teachers to adjust the use of learning media that is varied and in accordance with the characteristics of students in the 21st century era, such as utilizing multimedia in learning. The aim of this study is to improve student learning outcomes in the subject of Natural Science (IPAS) in grade V at SDN Pelandakan 2. This classroom action research was conducted in two cycles, each consisting of planning, action, observation, and reflection phases. Various types of multimedia, such as videos, animations, and interactive presentations, were used to deliver IPAS material with the aid of interactive Canva media and the use of Wordwall. The data were collected through learning outcome evaluation tests, observation of student activities, and student questionnaires regarding the use of multimedia, including interactive Canva media and Wordwall, in the learning process. Data analysis shows that the application of multimedia significantly improved students' understanding and learning outcomes. Before implementing multimedia, the average test score was 55.5, which increased to 78 in Cycle I and reached an average of 89 in Cycle II. Additionally, observations revealed increased participation and motivation among students during the learning process. This study recommends multimedia as an effective strategy to enhance the quality of IPAS teaching in primary schools.